2016
DOI: 10.1159/000450875
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Portuguese Patients with Chronic Hepatitis C

Abstract: Introduction: Chronic hepatitis C virus (HCV) infection impacts multiple health and psychosocial dimensions and encompasses a significant overall burden as it progresses to advanced stages of hepatic disease. Aims: To evaluate for the first time health-related quality of life (HRQoL) of a subset of Portuguese adult patients with chronic hepatitis C using the Portuguese versions of generic, Short-Form 12 Health Survey (SF-12v2), and disease-specific, Chronic Liver Disease Questionnaire (CLDQ), instruments; to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
9
1
2
Order By: Relevance
“…A hepatite perturba a vida quotidiana (Fédéra-tion SOS Hepatites, 2003;Körner, 2010;Rei et al, 2017). Além de provocar frequentemente cansaço crónico, obriga a um acompanhamento médico regular, que por sua vez reaviva o sentimento de se ser doente.…”
Section: Introductionunclassified
“…A hepatite perturba a vida quotidiana (Fédéra-tion SOS Hepatites, 2003;Körner, 2010;Rei et al, 2017). Além de provocar frequentemente cansaço crónico, obriga a um acompanhamento médico regular, que por sua vez reaviva o sentimento de se ser doente.…”
Section: Introductionunclassified
“…A review of neuropsychiatric symptoms commonly associated with HCV infection showed that major depression was related to illness perception, functional disability, impaired quality of life, fatigue severity, and the presence of psychiatric comorbidity [9] . Likewise, in the study of Rei et al [5] , there was a high prevalence of mood disorders (namely depression) with a negative impact on HRQoL, and the authors therefore recommend screening and suitable psychosocial interventions in a multidisciplinary setting.…”
mentioning
confidence: 99%
“…It reflects patient experience using surrogate markers such as health-related quality of life (HRQoL), functional status, perceived stigma, and work productivity [3,4] . In this context, the study by Rei et al [5] addresses an important topic and contributes to improve the scarce available Portuguese data. The main self-administered instruments used were the SF-12 (generic) and CLDQ (disease-specific) HRQoL questionnaires.…”
mentioning
confidence: 99%
“…We have read the article by Rei et al [1] about health-related quality of life valuation in patients with hepatitis C virus (HCV) infection. While we agree that it contributes to the subject knowledge, we think the selection of patients should be further discussed.…”
mentioning
confidence: 99%